The Digital Communication Media Reliance and its Implications on Students' Speaking Skills from The Perspective of Media System Dependency Theory - Baharman Baharman; Suriadi Suriadi (Ranah: Jurnal Kajian Bahasa, 2026)
The development of digital communication media has reshaped how students interact and practice speaking skills. This study aims to examine how dependency on digital communication media influences students’ face-to-face speaking skills by situating their language experiences within the framework of Media System Dependency Theory (Ball-Rokeach & DeFleur, 1976). The central problem addressed in this study arises from the growing comfort associated with speaking through digital media, which does not always correspond to readiness for speaking in offline contexts. This research adopts a qualitative approach with a descriptive–interpretative design. Data were obtained from reflective responses provided by 18 students and collected through an online open-ended questionnaire. The findings reveal three main results. First, digital communication media function as a means of emotional regulation by reducing anxiety and enhancing a sense of safety in speaking. Second, media dependency contributes to a shift in communication practices from face-to-face oral interaction to mediated communication, thereby reducing the intensity of direct speaking practice. Third, this shift has implications for decreased self-confidence, increased awkwardness, and reduced fluency in face-to-face speaking situations. The study concludes that media dependency shapes a contextual and performative orientation toward speaking. Theoretically, these findings extend Media System Dependency Theory into the field of language education by emphasizing that speaking skills constitute a linguistic practice shaped by systemic relations among individuals, media, and social contexts. Abstrak Perkembangan media komunikasi digital telah mengubah cara mahasiswa berinteraksi dan melatih keterampilan berbicara. Penelitian ini bertujuan untuk mengkaji bagaimana ketergantungan terhadap media komunikasi digital memengaruhi keterampilan berbicara tatap muka mahasiswa dengan menempatkan pengalaman berbahasa mereka dalam kerangka Media System Dependency Theory yang dikemukakan oleh Ball-Rokeach dan DeFleur (1976). Permasalahan utama dalam penelitian ini muncul dari meningkatnya kenyamanan berbicara melalui media digital yang tidak selalu sejalan dengan kesiapan berbicara dalam konteks luring. Penelitian ini menggunakan pendekatan kualitatif dengan desain deskriptif-interpretatif. Data diperoleh dari respons reflektif 18 mahasiswa yang dikumpulkan melalui kuesioner terbuka secara daring. Hasil penelitian menunjukkan tiga temuan utama. Pertama, media komunikasi digital berfungsi sebagai sarana regulasi emosional dengan mengurangi kecemasan dan meningkatkan rasa aman dalam berbicara. Kedua, ketergantungan media berkontribusi terhadap pergeseran praktik komunikasi dari interaksi lisan tatap muka menuju komunikasi bermedia sehingga mengurangi intensitas latihan berbicara secara langsung. Ketiga, pergeseran tersebut berdampak pada menurunnya rasa percaya diri, meningkatnya kecanggungan, dan berkurangnya kelancaran dalam situasi berbicara tatap muka. Penelitian ini menyimpulkan bahwa ketergantungan terhadap media membentuk orientasi berbicara yang bersifat kontekstual dan performatif. Secara teoretis, temuan ini memperluas Media System Dependency Theory ke dalam bidang pendidikan bahasa dengan menegaskan bahwa keterampilan berbicara merupakan praktik kebahasaan yang dibentuk oleh relasi sistemik antara individu, media, dan konteks sosial.